Penguatan Literasi Etika Dan Risiko Kecerdasan Artifisial Bagi Guru SMP Di Kabupaten Karawang - Uus Rusmawan; Tri Nur Arifin; Henri Septanto (Jurnal Pengabdian kepada Masyarakat UBJ, 2026)
The widespread use of Artificial Intelligence (AI) in education has brought significant changes and raised ethical challenges, such as data privacy risks, algorithmic bias, and potential breaches of academic integrity. This Community Service (PKM) activity aimed to strengthen the understanding of 30 junior high school teachers in Karawang Regency regarding the ethics and risks of using AI in learning. The implementation method applied a participatory action learning approach through three main stages: preparation, technical workshops (digital literacy, coding basics, and ethical AI), and post-training mentoring. The program evaluation results showed a measurable level of success. Teachers' cognitive understanding of the concepts and ethical implications of AI increased by 33,33%, as evidenced by an increase in the average pre-test score from 60 to 80 in the post-test. From a practical aspect, 100% (or 30 teachers) successfully developed outputs in the form of learning modules that integrate AI ethics into Informatics subjects. The final survey also showed that 95% of participants considered the program relevant and applicable, marked by the formation of a collaborative learning community among teachers. This program confirms that measurably strengthening AI ethics literacy for educators is crucial in preparing a responsible digital generation.